Species composition, distribution and biomass of macrofauna in the Visayas Sea. - Genito, Genibeth Espanueva
The macrobenthic fauna of the Visayan Sea water was investigated in this study as part of Project 3 of the DOST-PCAMRD funded pacific Seaboard R & D Program: Oceanographic Survey of Philippine Archipelagic waters in Central Philippines., Sediment samples were collected from 17 stations during the oceanographic cruise from 26 Apr -02 May 2001, using a Van Veen grab sampler. A total of 192 taxa were identified with overall mean density and biomass of 25, 450.8 ind/m squared respectively. The most abundant taxa include the foraminiferans, polychaetes and crustaceans. Relationships of macrofaunal density and biomass with depth, grain size, sorting index, % sand and % silt were determined.